Acute Stress Disorder Symptoms Predict All-Cause Mortality Among Myocardial Infarction Patients: a 15-Year Longitudinal Study. Issue 2 (27th October 2015) - Ginzburg, Karni; Kutz, Ilan; Koifman, Bella; Roth, Arie; Kriwisky, Michael; David, Daniel; Bleich, Avi
Abstract: Background: Studies have recognized myocardial infarction (MI) as a risk for acute stress disorder (ASD), manifested in dissociative, intrusive, avoidant, and hyperarousal symptoms during hospitalization. Purpose: This study examined the prognostic role of ASD symptoms in predicting all-cause mortality in MI patients over a period of 15 years. Methods: One hundred and ninety-three MI patients filled out questionnaires assessing ASD symptoms during hospitalization. Risk factors and cardiac prognostic measures were collected from patients' hospital records. All-cause mortality was longitudinally assessed, with an endpoint of 15 years after the MI. Results: Of the participants, 21.8 % died during the follow-up period. The decedents had reported higher levels of ASD symptoms during hospitalization than had the survivors, but this effect became nonsignificant when adjusting for age, sex, education, left ventricular ejection fraction, and depression. A series of analyses conducted on each of the ASD symptom clusters separately indicated that—after adjusting for age, sex, education, left ventricular ejection fraction, and depression—dissociative symptoms significantly predicted all-cause mortality, indicating that the higher the level of in-hospital dissociative symptoms, the shorter the MI patients' survival time. Conclusion: These findings suggest that in-hospital dissociative symptoms should be considered in the risk stratification of MI patients.